Potensi Mangrove dan Manfaatnya bagi Kelompok Etnik di Papua - Arobaya, Agustina; Pattiselanno, Freddy (Universitas Atma Jaya Yogyakarta, 2010)
significant contribution to those who living in and around mangrove forests. Like any othercommunities who occupied areas surrounding forest sites, Papuan ethnic groups really connectand integrate with the forest environment such as mangrove forests. This paper is a review ofrelated literatures that compiled from different research which have been conducted inUniversitas Negeri Papua (UNIPA) on utilization of mangrove by local ethnic groups and its rolefor other life biota in Papua. The results indicated that mangrove plays a very important rolefor local tribes in Papua as food sources, construction materials and source of energy,traditional medicine sources and wildlife habitat that are usually consumed by the communities.Ecology-based tourism or ecotourism as one leading sector of mangrove forests in Papua,though has a good potential, has not been optimizedly used.